The inhibitory effects of NKX3.1 on IGF-1R expression and its signalling pathway in human prostatic carcinoma PC3 cells - Zhang, Peng-Ju; Hu, Xiao-Yan; Liu, Chun-Yan; Chen, Zhao-Bo; Ni, Na-Na; Yu, Yang; Yang, Li-Na; Huang, Zhao-Qin; Liu, Qing-Wei; Jiang, An-Li (Asian journal of andrology, 2012)
NKX3.1, which is a prostate-specific homeobox gene, plays an important role in prostate cancer and usually functions as a tumour suppressor gene. In this study, we investigated the inhibitory effect of NKX3.1 on insulin-like growth factor (IGF)-1R expression and its downstream signalling pathway in PC3 cells. PC3 cells were stably transfected with NKX3.1 expression plasmid (pcDNA3.1-NKX3.1) or vector plasmid (pcDNA3.1+). The IGF-IR mRNA and protein expression levels were assessed in PC3-NKX3.1 transfectants by reverse transcriptase-polymerase chain reaction (RT-PCR) and Western blotting. The expression and activation of IGF-1/IGF-1R downstream signalling targets were examined by Western blotting and luciferase reporter assay. The cells were subsequently treated with relevant concentrations of IGF-1. The effect of IGF-1 on cell growth was examined by 3-(4,5)-dimethylthiahiazo(-z-y1)-3,5-diphenytetrazoliumromide (MTT) assay and flow cytometry analysis. A significant suppression of IGF-1R mRNA and protein expression was observed after forced expression of NKX3.1 in PC3 cells. Correspondingly, the forced expression of NKX3.1 decreased IGF-1-induced phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) and protein kinase B (AKT) and activation of the Elk-1 transcription factor and downregulated the expression of the downstream target genes c-fos and cyclin D1. Furthermore, the forced expression of NKX3.1 inhibited IGF-1-induced cell growth. In conclusion, NKX3.1 could downregulate IGF-1R expression and could inhibit IGF-1R-mediated mitogen-activated protein kinase (MAPK)/ERK and AKT signalling pathways, which might partially leads to the inhibition of IGF-1-induced cell growth. This study provides new insights into the molecular mechanisms that NKX3.1 exerts against prostate cancer and ultimately expands the scope of alternative approaches in advanced prostate cancer therapy.